Estratégias discursivas de mitigação na sequência discursiva de pergunta-resposta: a justificação no contexto de entrevista - Almeida, Carla Aurélia de (2017)
Taking as reference an oral corpus of narratives of life experience collected in interviews, we will analyse the question-answer sequence and the justification sequence. As a pre-sequence that prepares the act of question, anticipating possible objections from the interviewee, justification constitutes an argumentative strategy, developed by the interviewer, at the service of interactional achievement. We will also study the interviewees' answers followed by justification, specifically those at the service of the mitigation of epistemic values, representing a strategy of mitigation and softening what is being said in the propositional content of the answer, reducing the epistemic obligations of the interviewee.